Drift : Illicit Mobility and Uncertain Knowledge - Ferrell, Jeff (Book collections on Project MUSE., 2018)
This book shows how dislocation and disorientation can become phenomena in their own right. Examining the history of drifting, the author situates the global phenomenon of drift within early 21st century economic, social, and cultural dynamics. He then highlights a distinctly North American form of drift--that of the train-hopping hobo--by tracing the hobo's political history and by sharing his own immersion in the world of contemporary train-hoppers. Along the way, the author sheds light on the ephemeral intensity of drifting communities and explores the contested politics of drift--the legal and political strategies designed to control drifters in the interest of economic development, the irony by which these strategies spawn further social and spatial exclusion, and the ways in which drifters and those who embrace drift create their own slippery strategies of resistance. With an eye toward the truth, the author argues that the lessons of drift can provide us with new models for knowing and engaging with the world around us.--Adapted from information provided by publisher.